2006
DOI: 10.1091/mbc.e05-08-0775
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Histone Deacetylase 4 Expression by the SP Family of Transcription Factors

Abstract: Histone deacetylases mediate critical cellular functions but relatively little is known about mechanisms controlling their expression, including expression of HDAC4, a class II HDAC implicated in the modulation of cellular differentiation and viability. Endogenous HDAC4 mRNA, protein levels and promoter activity were all readily repressed by mithramycin, suggesting regulation by GC-rich DNA sequences. We validated consensus binding sites for Sp1/Sp3 transcription factors in the HDAC4 promoter through truncatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 84 publications
4
38
0
Order By: Relevance
“…Because class IIa HDACs have been reported to be expressed in a tissue-specific manner (Wang et al, 1999;Liu et al, 2006), we first confirmed the expression of HDAC4 in normal intestinal epithelium. Although considerable variability in HDAC4 protein expression was observed among a panel of different mouse tissues, robust HDAC4 expression was detected in the small intestine and colon ( Figure 1A).…”
Section: Robust Hdac4 Expression In Normal Intestine and In Colon Canmentioning
confidence: 70%
See 2 more Smart Citations
“…Because class IIa HDACs have been reported to be expressed in a tissue-specific manner (Wang et al, 1999;Liu et al, 2006), we first confirmed the expression of HDAC4 in normal intestinal epithelium. Although considerable variability in HDAC4 protein expression was observed among a panel of different mouse tissues, robust HDAC4 expression was detected in the small intestine and colon ( Figure 1A).…”
Section: Robust Hdac4 Expression In Normal Intestine and In Colon Canmentioning
confidence: 70%
“…Mithramycin is an established inhibitor of the binding of transcription factors, such as Sp1, to GC-rich elements (Liu et al, 2006). As shown in Figure 9A, siHDAC4 was unable to stimulate p21 expression in the presence of mithramycin.…”
Section: A J Wilson Et Almentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, we have found that PTH induces HDAC4 gene expression and enzymatic activity in osteoblastic cells. The rat HDAC4 promoter has not been identified yet, but we have conducted homology searches of the human HDAC4 promoter that Liu et al (35) have reported. The human HDAC4 promoter has GC-rich DNA sequences, which bind Sp-1/Sp-3.…”
Section: Discussionmentioning
confidence: 99%
“…To get an indication whether the GC-rich sites influence CD97 transcriptional regulation, we treated cell cultures with mithramycin, a cell-permeable agent that binds to GC-rich DNA sequences and that is frequently used to explore the sequence dependency of DNA-binding 11 factors (Liu et al, 2006). Since CD97 promoter activities as well as mRNA expression levels were decreased by mithramycin in SMCs, we studied the GC-sites in more detail using reporter gene assays as well as gelshift and ChIP analysis.…”
Section: Discussionmentioning
confidence: 99%